Modeling the potential impact of rectal microbicides to reduce HIV transmission in bathhouses - Romulus Breban; Ian McGowan; Chad Topaz; Elissa J. Schwartz; Peter Anton; Sally Blower (Mathematical Biosciences and Engineering)
We evaluate the potential impact of rectal microbicides for reducing HIVtransmission in bathhouses. A new mathematical model describing HIV transmissiondynamics among men who have sex with men (MSM) in bathhouses is constructed and analyzed.The model incorporates key features affecting transmission, including sexual rolebehavior (insertive and receptive anal intercourse acts), biological transmissibilityof HIV, frequency and efficacy of condom usage, and, most pertinently, frequency andefficacy of rectal microbicide usage. To evaluate the potential impact of rectalmicrobicide usage, we quantify the effect of rectal microbicides (ranging in efficacyfrom 10% to 90%) on reducing the number of HIV infections in the bathhouse.We conduct uncertainty analyses to assess the effect of variability in both biologicaland behavioral parameters. We find that even moderately effective rectalmicrobicides (if used in 10% to 50% of the sex acts) would substantially reducetransmission in bathhouses. For example, a 50% effective rectal microbicide (usedin 50% of sex acts) would reduce the number of secondary infections by almost 13% atdisease invasion. Our modeling analyses show that even moderately effective rectalmicrobicides could be very effective prevention tools for reducing transmission inbathhouses and also potentially limit the spread of HIV in the community.